THE EFFECT OF USING SOCRATIC METHOD ON THE STUDENTS’ACHIEVEMENT IN SPEAKING AT THE JUNIOR HIGH SCHOOL MTSN 1 BANDAR MASILAM - Rali Aray, Havivah Hajar (Faculty of Tarbiyah nad Teacher Training, 2022)
The researcher interested to conduct two things namely academic year 2020/ 2021 The Effect of Using Socratic Method on The Students’ Achievement in Speaking at Junior High School MTsN 1 Bandar Masilam. This type of research is a quasi experimental, with the sampling technique using cluster random sampling. The two classes that became the research were the experimental class VIII 2 and the control class VIII 3 which were suitable for each of the 30 students. The learning outcome data in the study were obtained using pre-test and post-test. The results of the study, the pretest mean value of the experimental class and the control class respectively were 34.5 and 33.5, then the data prerequisite test was carried out, namely the normality test and the homogeneity test of the data obtained by Lhitung<Ltabel (0.0961 <0.161) for the experimental class. And 0.0815 <0.1610 for the control class so that the pretest data from both classes were normally distributed. Fcount<F (1.27 <1.94), then the sample used in the study was stated to be homogeneous, after being treated the posttest results of the experimental class were 73.16 and the control class 69.66. The average student learning activity is 64.92 which is classified as active. Hypothesis testing was carried out using the t test, it was obtained tcount = 2.42 and ttable = 1.68 so that tcount>ttable then Ha was accepted so that it could prove that there was damage due to the influence of the use of the Socrates method on student speaking in class VIII semester I MTSN Negeri 1 Bandar Masilam TP 2020/2021.